PENGEMBANGAN MAKANAN PENDAMPING AIR SUSU IBU (MPASI) BERBASIS PUPA MULBERRY (PURY) - Astuti, Trina; Kusharto, Clara M; ., Hardinsyah; Firmansyah, Agus (PERSATUAN AHLI GIZI INDONESIA, 2009)
COMPLEMENTARY FOOD DEVELOPMENT BASED ON PUPAE-MULBERRY (PURY)Proper complementary feeding are well recognized as necessary to ensure optimal growth anddevelopment during the early years, however are often inadequate in energy density, protein andmicronutrient concentration. The aim of the study is to develop pury-formula complementary foodsfor infant aged 6-9 moths and to analyze nutrition quality and food safety. A silkworm pupae was amajor constituents used as materials which was processed to be a fine powder, called “PURY”.Methods: mix all ingredients consist of 16.6% red rice flour, 16.6% tempe powder, 16.6% formula milkpowder, 25% fine sugar cane and 25% pury. Results and finding: Per 100 g Pury-formula contain 426kcal energy, 20.0% protein, 11.2% fat included linoleat and linolenat; vitamin A,E, B groups andmineral such as Fe, Ca, Zinc, Iodine and Se. Conclusion: Pury-formula complementary food is betterthan commercial product and as well as Health Department guidance. It has a well balanced amountof energy, protein, carbohydrate, fat included long chain polyunsaturated fatty acids (LC-PUFAs) thatare essential for the brain and optimal growth of infants. Recommendation: Pury-formula can be analternate nutritious complementary food for infants undernourished.Keywords: pury, complementary food, growth, infant, undernourished